Gelin-Cesáro identities for Fibonacci and Lucas quaternions - Ahmet Daşdemir (Walter de Gruyter GmbH, 2019)
Abstract To date, many identities of different quaternions, including the Fibonacci and Lucas quaternions, have been investigated. In this study, we present Gelin-Cesáro identities for Fibonacci and Lucas quaternions. The identities are a worthy addition to the literature. Moreover, we give Catalan’s identity for the Lucas quaternions.
Keywords: catalan’s identity; Catalan's identity; fibonacci quaternion; QA1-939; Fibonacci and Lucas numbers and polynomials and generalizations; Gelin-Cesáro identity; Fibonacci quaternion; Mathematics; gelin-cesáro identity